Assessing the Tensile Shear Strength and Interfacial Bonding Mechanism of Poplar Plywood with High-density Polyethylene Films as Adhesive - Liang Chang; Wenjing Guo; Qiheng Tang (BioResources, 2016)
A series of high-density polyethylene (HDPE) films were tested as adhesives for plywood and were fabricated using hot pressing followed by cold pressing. The effects of the moisture content, HDPE dosage, and the hot-press temperature and pressure on the mechanical properties were evaluated by analyzing the tensile shear strength. The results indicated that the HDPE films that were used as adhesives in plywood had good bonding strength, meeting the requirements for type II-grade plywood according to the GB/T 9846.3 standard (2004, Beijing, China). The bonding mechanism was also investigated using the width of the bond line, the average penetration (AP), and the effective penetration (EP) through the use of optical microscopy and scanning electron microscopy (SEM). The results showed that the HDPE is able to penetrate into the vessels, xylem, and so on. On the whole, both the AP and EP increased with an increase in the HDPE dosage and hot-press temperature and pressure, but not with an increase in the moisture content. In addition, the effects of the factors mentioned above on the width of the bond line, AP, and EP were also investigated by an ANOVA analysis.